The relationship between perifoveal capillary ring alterations and visual acuity in diabetic retinopathy - Petrović, Nenad; Todorović, Dušan; Srećković, Sunčica; Šarenac Vulović, Tatjana; Jovanović, Svetlana; Paunović, Svetlana; Vulović, Dejan; Randjelović, Danijela (Vojnosanitetski pregled, 2022)
Background/Aim. The relationship between the foveal avascular zone (FAV) and visual acuity (VA) in retinal diseases remains a matter of discussion. The aim of this study was to determine the impact of diabetic macular ischemia (DMI) on VA through the analysis of the perifoveal capillary network in various stages of diabetic retinopathy - DR (non-proliferative diabetic retinopathy – NPDR and proliferative diabetic retinopathy – PDR). Methods. Qualitative and quantitative analysis of 143 angiograms of patients with different stages of DR was performed. The degree of macular ischemia was assessed by the analysis of 2 parameters: perifoveal capillary ring, ie, the FAZ outline irregularity, and capillary loss. Finally, a comparison was made between the degree of macular ischemia with the best-corrected VA, depending on macular thickness. Results. In the eyes with mild and moderate NPDR, without significant macular thickening, no statistically significant decrease in VA caused by macular ischemia was noticed (p = 0.81). Opposite, in a subgroup with severe NPDR and PDR, without significant macular thickening, a statistically significant difference was presented among eyes with moderate and severe macular ischemia compared to eyes with lower grades of macular ischemia (p = 0.021 and p = 0.018, respectively). In the eyes with moderate NPDR and mild macular ischemia, the increase in macular thickness resulted in a statistically insignificant decrease in VA compared to eyes with a normal macular thickness (p = 0.088). However, in the eyes with severe NPDR, every pathological increase in macular thickness caused a statistically significant decrease in VA, regardless of the degree of macular ischemia (p = 0.018–0.040). A similar relationship was also found in the eyes with PDR (p = 0.017–0.042). In the eyes with a statistically significant decrease in VA, most of the examined eyes (98%) had the FAZ outline irregularity in the nasal perifoveal subfield. Conclusion. In the absence of significant macular thickening, the destruction of one-half of the perifoveal capillary network, or greater, is associated with reduced VA. The location of macular ischemic changes in the nasal parts of the perifoveal capillary ring plays a crucial role in its effects on visual function.